Illustrated guide to the emerald ash borer Agrilus planipennis Fairmaire and related species (Coleoptera, Buprestidae) - Xing-Ke Yang (Pensoft Publishers, 2015)
The 33 species of Agrilus (Coleoptera: Buprest idae) hypothesized to be most closely related or most similar to Agrilus planipennis Fairmaire (emerald ash borer, EAB), are described and illustrated. Morphology (adults and immatures), biology, distribution, detailed taxonomic history and systematics are presented for each species, along with a full literature review and bibliography. Large, high resolution photos displaying all diagnostic characters are presented as well as an illustrated dichotomous identification key to adult species of Agrilus treated in this work. A general review of Agrilus biology, ecology and buprestid collecting and curation methods is also provided.